Odpowiedź:
Szczegółowe wyjaśnienie:
Zad. 1
4x
Zad. 2
a) 10a+3
[tex]b) (8k)^{2}[/tex]
c) 0,6t
Zad. 3
6a-7a+a-2a= -2a Odp.C
Zad.4
(6x-5)-(3+x)=6x-5-3-x=5x-8 Odp.C
Zad.5
[tex]\frac{1}{6} (12a+6b-18)=\frac{1}{6} *12a+\frac{1}{6}*6b-\frac{1}{6}*18= 2a+b-3[/tex]
[tex]\frac{8x+12y-4}{4} =\frac{8x}{4} +\frac{12y}{4} -\frac{4}{4} = 2x+3y-1[/tex]
[tex]4x+5-\frac{15x-18}{3} = 4x+5- (\frac{15x}{3} -\frac{18}{3} )=4x+5-5x+6=-x+11[/tex]
Zad. 6
(7x-5y)(7x+5y)=7x*7x+7x*5y-5y*7y-5y*5y=
[tex](7x-5y)(7x+5y)=7x*7x+7x*5y-5y*7y-5y*5y= 49x^{2} +35xy-35xy-25y^{2} =49x^{2} -25y^{2} Odp. D[/tex]